Dracaena Mannii Leaf Meal Supplementation in Broiler Chicks: Effects on Growth Performance, Haematology and Serum Biochemical Indices - John, Alagbe Olujimi (MultiTech Publisher, 2024)
The study aimed to investigate the impact of Dracaena mannii leaf meal on the growth performance and haematological and biochemical indices of Hubbard broiler chicks. 200 chicks were divided into four groups, each with a different diet. The diets were based on corn-soya meal without Dracaena mannii leaf (DMF), with DMF added at different amounts. The study found that DMF contained flavonoids, phenols, tannins, alkaloids, steroids, and saponins. The average daily feed intake was similar in diets 3 and 4, but significantly higher than in diets 1 and 2, with no mortality recorded. The diets significantly influenced pack cell volume, red blood cell, haemoglobin, white blood cell, leucocytes, and monocyte counts, but within the optimal range for healthy birds. The study concluded that DMF supplementation up to 600 g can optimize broiler performance without negatively impacting their health status.The study aimed to investigate the impact of Dracaena mannii leaf meal on the growth performance and haematological and biochemical indices of Hubbard broiler chicks. 200 chicks were divided into four groups, each with a different diet. The diets were based on corn-soya meal without Dracaena mannii leaf (DMF), with DMF added at different amounts. The study found that DMF contained flavonoids, phenols, tannins, alkaloids, steroids, and saponins. The average daily feed intake was similar in diets 3 and 4, but significantly higher than in diets 1 and 2, with no mortality recorded. The diets significantly influenced pack cell volume, red blood cell, haemoglobin, white blood cell, leucocytes, and monocyte counts, but within the optimal range for healthy birds. The study concluded that DMF supplementation up to 600 g can optimize broiler performance without negatively impacting their health status.